Training for agricultural entrepreneurship: a bibliometric analysis - Cortés Rodríguez1, Carlos Alberto; Martínez-Gómez, Gladys; Vega-Martínez, Daniel; Sangerman Jarquín, Dora Maria (Revista Mexicana de Ciencias Agrícolas, 2022)
Agricultural entrepreneurship is one of the factors that influence job creation, economic income and competitiveness of the agricultural sector. Due to the relevance of the topic, it is important to explore the literature of recent years and identify the business skills that farmers can develop through training for the success of their business initiatives. The objective of this work is to present a bibliometric analysis to measure scientific production and reveal training topics for agricultural entrepreneurship. The information search was carried out in the Scopus and Web of Science databases in the period 2010-2020. The delimitation of the thematic groups was achieved by VOSviewer, based on the bibliometric technique of co-occurrence of terms. It was found that published papers increased in recent years and four thematic groups on the development of agricultural business skills were identified. The findings of this research can be used for the design of training courses or can guide the design of public policies that strengthen the agricultural sector.
Keywords: agriculture; business skills; literature review